Impact of Different Salinity Levels on the Germination and Survival of Grey Mangrove Avicennia marina Seedlings in Tajoura, Libya (Al-Farooq Journal of Sciences, 2026)
Early germination represents one of the most critical stages in the lifecycle of mangroves, as it is highly sensitive to salinity levels. This study aimed to evaluate the impact of different salinity concentrations on the germination and survival of Grey Mangrove (Avicennia marina) seedlings along the Libyan coast. The experiment was conducted in Tajoura, Tripoli, over a period of one month, utilizing three treatments: freshwater (100 mg/L; T1), a mixture of freshwater and seawater (approximately 17,500 mg/L; T2), and full seawater (approximately 35,000 mg/L; T3), with 12 seedlings per treatment.Results indicated that all seedlings in T1 survived (100% survival rate) without exhibiting stress symptoms. In contrast, only 41.7% of seedlings in T2 survived, with the appearance of salt crystals on the stems, indicating significant salt stress. T3 recorded total mortality (0% survival rate). Statistical analysis using One-way ANOVA revealed a highly significant effect of salinity levels on seedling survival (F = 34.26, exceeding the critical value; P < 0.001).These findings highlight the acute impact of salinity on survival during early germination stages, suggesting that survival rates can be optimized through the use of freshwater or gradual salinity acclimation. This study provides crucial empirical data for coastal afforestation programs in Libya and contributes to designing salinity management strategies to enhance the success of mangrove development projects.
Keywords: Grey mangrove, seed germination, seedling survival, salinity stress, coastal restoration, Libya